Assessment of the Accuracy in Measuring the Enamel Thickness of Maxillary Incisors with Optical Coherence Tomography - Hiroshi Miyagi; Kyosuke Oki; Yoshihiro Tsukiyama; Yasunori Ayukawa; Kiyoshi Koyano (Diagnostics, 2022)
Although the clinical assessment of enamel thickness is important, hardly any tools exist for accurate measurements. The purpose of this study was to verify the precision of enamel thickness measurements using swept-source optical coherence tomography (SS-OCT). Human extracted maxillary central and lateral incisors were used as specimens. Twenty-eight sites were measured in each specimen. The optical path length (OPL) at each measurement site was measured on the OCT images, and enamel thickness (e1) was calculated by dividing OPL by the mean refractive index of enamel, 1.63. The specimens were then sectioned, and a light microscope was used to measure enamel thickness (e2). e1 and e2 were then compared. Measurement errors between e1 and e2 for the central and lateral incisors were 0.04 (0.02; 0.06) mm and 0.04 (0.02; 0.07) mm [median value: (25%, 75% percentile)], respectively. No significant differences between measurement sites were noted for measurement errors between e1 and e2. These results demonstrate that OCT can be used for noninvasive, accurate measurements of enamel thickness.